Experimental Investigation on Influence of Biochar on the Impact Properties of Novel Jute Fiber Reinforced Epoxy Composite (Journal of Pharmaceutical Negative Results, 2022)
Aim: Biochar is the sustainable material addition of biochar that could significantly vary the composite strength. Hence biocharis eco friendly it causes no effect to the environment further it increases the chance of developing sustainable composites withincreased mechanical strength. The goal of this study is to investigate the impact strength of a novel biochar-added jute fiber composite. Materials and Methods: By the utilization of hand lay up technique composites were fabricated into two distinctive groups (Experimental and control group). The sample groups were tested according to the ASTM-D256 protocol. The Izod impact testing was used to find the impact strength of the samples. For experimentation sample size was calculated using the G-power calculator at 80% of G-power value. The independent sample T-test was done using SPSS software for analyzing the impact strength variation. In both the groups 20 samples were tested using the SPSS tool. Result: The samples with and without filler were tested and their impact strength was calculated and compared. Sample with the novel biochar filler showed higher impact strength. The mean impact strength was 29 J/m which was 21 % higher than the unfilled composite. The p value noted was 0.043 which was significant (p<0.05) at 95% significance level. Conclusion: Within the limitations of the study, the result revealed that the hybrid composite with 5% of biochar filler possesses the maximum impact strength than the composite created without filler material. This demonstrates the ability of the novel biochar particle in the composites for the development of impact resistance.